Epiproct and dorsal process structure in the Allocapnia forbesi Frison, A. pygmaea (Burmeister), and A. rickeri Frison species groups (Plecoptera: Capniidae), and inclusion of A. minima (Newport) in a new species group - Stark, Bill P. (Illiesia, 2012)
Epiprocts and tergal processes for males of twenty Allocapnia species assigned to the A. forbesi Frison, A. pygmaea (Burmeister), and A. rickeri Frison groups were examined with scanning electron microscopy. Results suggest these groups are closely related and that A. minima (Newport) should be excluded from the A. forbesi group and assigned to its own group.
Keywords: Allocapnia; entomology; Male Genitalic Structures; Plecoptera; Scanning Electron Microscopy